2021
DOI: 10.3390/microorganisms9081548
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Stage-Specific Fecal Bacterial Community Fingerprinting of the Taiwanese Population and Underpinning of Potential Taxonomic Biomarkers

Abstract: Despite advances in the characterization of colorectal cancer (CRC), it still faces a poor prognosis. There is growing evidence that gut microbiota and their metabolites potentially contribute to the development of CRC. Thus, microbial dysbiosis and their metabolites associated with CRC, based on stool samples, may be used to advantage to provide an excellent opportunity to find possible biomarkers for the screening, early detection, prevention, and treatment of CRC. Using 16S rRNA amplicon sequencing coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 107 publications
(141 reference statements)
4
17
0
Order By: Relevance
“…Dorea can adhere to cancer cells and may give this genus a competitive advantage in the cancerous CRC environment [36]. A study of 17 healthy controls, 21 polyps patients, and 21 cancer patients in Taiwan indicated that Dorea had significant superiority in CRC prediction [37], which is also reflected in our research.…”
Section: Discussionsupporting
confidence: 76%
“…Dorea can adhere to cancer cells and may give this genus a competitive advantage in the cancerous CRC environment [36]. A study of 17 healthy controls, 21 polyps patients, and 21 cancer patients in Taiwan indicated that Dorea had significant superiority in CRC prediction [37], which is also reflected in our research.…”
Section: Discussionsupporting
confidence: 76%
“…The F/B ratio is reflective of the balance of intestinal symbiotic microbiota. The F/B ratio has been studied in not only intestinal diseases such as IBD [ 8 ], but also in metabolic diseases such as obesity, NAFLD, inflammatory diseases, and cancers [ 12 , 22 ]. Intestinal microbiota can affect the entire body.…”
Section: Discussionmentioning
confidence: 99%
“…have been considered to be bioindicators of human health; the risk of CRC or IBD is increased when their abundance levels are lower than those in healthy individuals ( Ferreira-Halder et al, 2017 ; Lawrence et al, 2020 ). Additionally, it was shown that the abundance of genus Odoribacter was decreased in the patients of CRC and polyps as compared with the control group ( Fang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%